2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090847
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-selective recording from peripheral nerves using a multiple-contact cuff: Report on pilot pig experiments

Abstract: A single cuff electrode with multiple-contacts permits fibre selective recording from peripheral nerves. This has been demonstrated in frog nerve in vitro and earth worm before. In this paper we apply this method successfully to the peripheral median nerve of pig in vivo. Compound action potentials (CAPs) were electrically excited at the median nerve close to the wrist of the forelimb. The CAPs were recorded by a recording nerve cuff located proximal to the stimulation cuff. Applying simple mathematical routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Inspection of the biologically plausible range of velocities (0 m s -1 -100 m s -1 ) showed the main populations to be in the range of 5 m s -1 -20 m s -1 . The sampling rate used is considerably higher than in previous work and so there is no requirement to interpolate the data [6]. It should be noted that the relationship between the delay size dt and the velocity is not linear and so there is greater resolution at lower velocities [9].…”
Section: Recording Electronics and Data Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Inspection of the biologically plausible range of velocities (0 m s -1 -100 m s -1 ) showed the main populations to be in the range of 5 m s -1 -20 m s -1 . The sampling rate used is considerably higher than in previous work and so there is no requirement to interpolate the data [6]. It should be noted that the relationship between the delay size dt and the velocity is not linear and so there is greater resolution at lower velocities [9].…”
Section: Recording Electronics and Data Analysismentioning
confidence: 96%
“…However, although multiple electrode cuffs (MECs) have been used to record electrically evoked compound action potentials (CAPs) [6], [7], VSR has, until now, not been demonstrated with naturally-occurring neural signals. This paper presents experimental data that supplements and extends earlier work using CAPs as described in [6] and [7] and provides the first practical demonstration of the application of VSR to naturally-occurring ENG. Unlike the recordings reported in [2] - [4] experiments described in this paper used an array of hook electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recording of bladder sensory information has been attempted using cuffs in anesthetized humans (21), but the signal size (5 mV, SNR = 0.2) is insufficient for use while awake and moving. Techniques under development include velocity-selective recordings from multielectrode cuffs to generate a more detailed action potential profile (25,26), but these currently require a very high sampling rate and detailed offline analysis (27).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported neural amplifiers [107, 134] that employ the velocity selection recording (VSR) technique, first proposed in [106], to selectively amplify weak PNS signals with differing conduction velocities. The ability of VSR to discriminate recorded activity based on fiber type has been validated in several acute in vivo studies [123, 124, 153]; demonstrating this technique in a chronically implanted model would represent a major advancement.…”
Section: Applications Of Neural Amplifiersmentioning
confidence: 99%